A morphological analysis of spotted-winged fruit bat (pteropodidae : balionycteris naculata) in Malaysia - Naharuddin, N.M (Universiti Malaysia Sarawak (UNIMAS), 2013)
A morphological analysis of 30 individuals of the spotted-winged fruit bat, Balionycteris maculata was performed using 14 external characters and 18 craniodental characters. All the individuals were from three different populations that included Sarawak, Sabah and Pahang population. Discriminant function analysis was done for separated both external and craniodental characters. The D3MCL was suggested as the best predictors for the external characters while DL for the craniodental characters in differentiating the B. maculata from different population.